2020
DOI: 10.1097/jcp.0000000000001245
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Fluvoxamine for Schizophrenia: A Meta-analysis of Randomized Double-Blind, Placebo-Controlled Trials

Abstract: Background This was a meta-analysis of double-blind, randomized controlled trials that examined the therapeutic effects and tolerability of adjunctive fluvoxamine versus placebo for schizophrenia. Methods The Review Manager, Version 5.3, was used to analyze data. Results Five double-blind randomized controlled trials (N = 284) covering 145 patients on adjunctive fluvoxamine and 139 patients on placebo were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Regarding antidepressants, a recent meta-analysis [ 82 ] considering the effects of adjunctive fluvoxamine, included five randomized controlled trials (284 participants), two of which also evaluated cognitive outcomes, and observed no significant pro-cognitive effect of the antidepressant drug. A Cochrane Collaboration meta-analysis [ 83 ] focused on adjunctive mirtazapine and included nine randomized controlled trials (310 participants): four studies reported data on cognitive outcomes, three of which were included in the systematic evaluation of cognition, and, although minimal positive effects were reported in one trial, no substantial improvement in cognition was observed.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Regarding antidepressants, a recent meta-analysis [ 82 ] considering the effects of adjunctive fluvoxamine, included five randomized controlled trials (284 participants), two of which also evaluated cognitive outcomes, and observed no significant pro-cognitive effect of the antidepressant drug. A Cochrane Collaboration meta-analysis [ 83 ] focused on adjunctive mirtazapine and included nine randomized controlled trials (310 participants): four studies reported data on cognitive outcomes, three of which were included in the systematic evaluation of cognition, and, although minimal positive effects were reported in one trial, no substantial improvement in cognition was observed.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…We suggest that the FIASMA-antidepressants may thus be expected to benefit patients with schizophrenia. Considering the inconsistent results among previous clinical trials and investigations on the FIASMA antidepressant fluvoxamine adjunctive therapy for patients with schizophrenia [60][61][62], it is worthy investigating whether FIASMAs may have therapeutic effect on a group of patients with schizophrenia or combined depressive disorders who present abnormal ASM/ceramide system. We also propose future directions from the biological landscape for the development of new treatments for schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…FIASMAs induce the detachment of ASM from inner lysosomal membranes and thereby cause its consecutive inactivation [59]. However, clinical trials of adjunctive therapy using the FIASMA-antidepressant fluvoxamine to treat schizophrenia have given inconsistent results [60][61][62]. Because the activated ASM/ceramide system may be inhibited by approved FIASMAs and particularly by the antidepressants in this drug class, FIASMAs may be expected to benefit patients with schizophrenia or combined depressive disorders who have ASM/ceramide system dysfunction and abnormal ceramide levels.…”
Section: Introductionmentioning
confidence: 99%